P-I metalloproteinases and L-amino acid oxidases from Bothrops species inhibit angiogenesis - Bhat, Shreesha K.; Joshi, Manjunath B.; Vasishta, Sampara; Jagadale, Rajesh N.; Biligiri, Setlur G.; Coronado, Monika A. [UNESP]; Arni, Raghuvir K. [UNESP]; Satyamoorthy, Kapaettu (FapUNIFESP (SciELO), 2021)
Background: Snake venoms are composed of pharmacologically active proteins that are evolutionarily diverse, stable and specific to targets. Hence, venoms have been explored as a source of bioactive molecules in treating numerous diseases. Recent evidences suggest that snake venom proteins may affect the formation of new blood vessels. Excessive angiogenesis has been implicated in several pathologies including tumours, diabetic retinopathy, arthritis, inter alia. In the present study, we have examined the effects of P-I metalloproteinases isolated from Bothrops moojeni (BmMP-1) and Bothrops atrox (BaMP-1) and L-amino acid oxidases (LAAO) isolated from B. moojeni (BmLAAO) and B. atrox (BaLAAO) on biochemical and functional aspects of angiogenesis. Methods: P-I metalloproteinases and LAAO were purified from venom by molecular size exclusion and ion-exchange chromatography and subsequently confirmed using mass spectrometry. The P-I metalloproteinases were characterized by azocaseinolytic, fibrinogenolytic and gelatinase activity and LAAO activity was assessed by enzyme activity on L-amino acids. Influence of these proteins on apoptosis and cell cycle in endothelial cells was analysed by flow cytometry. The angiogenic activity was determined by in vitro 3D spheroid assay, Matrigel tube forming assay, and in vivo agarose plug transformation in mice. Results: P-I metalloproteinases exhibited azocaseinolytic activity, cleaved α and partially β chain of fibrinogen, and displayed catalytic activity on gelatin. LAAO showed differential activity on L-amino acids. Flow cytometry analysis indicated that both P-I metalloproteinases and LAAO arrested the cells in G0/G1 phase and further induced both necrosis and apoptosis in endothelial cells. In vitro, P-I metalloproteinases and LAAO exhibited significant antiangiogenic properties in 3D spheroid and Matrigel models by reducing sprout outgrowth and tube formation. Using agarose plug transplants in mice harbouring P-I metalloproteinases and LAAO we demonstrated a marked disruption of vasculature at the periphery. Conclusion: Our research suggests that P-I metalloproteinases and LAAO exhibit anti-angiogenic properties in vitro and in vivo.
Keywords: Anti-angiogenic; Bothrops; LAAO; P-I metalloproteinases; Snake venom